Molecular mechanisms of mTOR-mediated cisplatin response in tumor cells - Amirhosein Maharati; Yasamin Rajabloo; Meysam Moghbeli (Heliyon)
Cisplatin (CDDP) is one of the main chemotherapeutic drugs that is widely used in many cancers. However, CDDP resistance is a frequent therapeutic challenge that reduces prognosis in cancer patients. Since, CDDP has noticeable side effects in normal tissues and organs, it is necessary to assess the molecular mechanisms associated with CDDP resistance to improve the therapeutic methods in cancer patients. Drug efflux, detoxifying systems, DNA repair mechanisms, and drug-induced apoptosis are involved in multidrug resistance in CDDP-resistant tumor cells. Mammalian target of rapamycin (mTOR), as a serine/threonine kinase has a pivotal role in various cellular mechanisms such as autophagy, metabolism, drug efflux, and cell proliferation. Although, mTOR is mainly activated by PI3K/AKT pathway, it can also be regulated by many other signaling pathways. PI3K/Akt/mTOR axis functions as a key modulator of drug resistance and unfavorable prognosis in different cancers. Regarding, the pivotal role of mTOR in CDDP response, in the present review we discussed the molecular mechanisms that regulate mTOR mediated CDDP response in tumor cells.